The presence of Algarve wine producers on Facebook between pre-covid-19 and covid-19 periods - Almeida, Carlos M.; Afonso, Carlos M.; Serra , Manuel; António , Nuno (Tourism and Hospitality International Journal, 2024)
Social media may be used to build virtual communities around brands, allowing consumers to learn more about them and interact with the material they provide. In this sense, it serves as a helpful communication medium for obtaining and disseminating information about wine as a social commodity, affecting wine consumers' purchasing decisions. The number of Algarve wine producers has increased in recent years, indicating the sector's progress. Wine is one of the most popular internet products, and social media sites like Facebook are ideal for promoting it. Thus, the objective of this study is to analyze the evolution of the usage of Algarve wine producers on their Facebook pages between February 2019 and the end of January 2022, corresponding to a pre-Covid-19 period and the Covid-19 period. To do this, we used the model developed by Huertas, Setó-Pàmies & Míguez-González (2015), where the variables of “Contents”, “Interactivity”, “Visibility” are considered, with an additional variable for “Profitability”, referenced by Rodríguez-Fernandez et al. (2017b). The analysis was made through a series of performance indicators collected using the online data collection tool Fanpage Karma. Results have shown a greater effort from some of these pages to produce content more often, specially at the beginning of the Covid-19 pandemic period, while some are still struggling to explore this medium, but overall there is room to be more active and productive in social media networks since these pages frequency of publication is low. In need to adjust their communication strategies, the most active pages grew a lot in numbers of fans, reactions, and other interactions, producing quality content that engaged consumers. The less explored pages show smaller evolution, from which we can conclude that there is still potential in Facebook as a platform for the wine sector.